Conversor CC-CC híbrido SEPIC com saídas simétricas integrado a célula a capacitor chaveado modificada - Sebaje, Alex Sander (2023)
In this paper, the topology study of a non-isolated hybrid DC-DC converter formed by integrating a SEPIC (PWM) converter with symmetrical voltage outputs integrated with modified switched capacitor cell operating in (CCM) continuous conduction mode is presented. The converter is suitable for connecting a battery energy storage system in a DC microgrid or in renewable energy solutions, electric mobility and electrification of transport means using energy storage. Due to the switchedcapacitor cell concept, the proposed topology allows working with higher output voltages, allowing the semiconductors to be subjected to reduced voltage stress compared to the conventional SEPIC converter. The work presents the qualitative analysis of the converter with the description of the operating principle, ideal waveforms, quantitative analysis to obtain the design equations. In a second moment of the work, the proof of the study is presented with the numerical simulation results and later experimental tests of the converter operating with 240V input voltage, 400V output voltage, 50kHz switching frequency and nominal power of 1KW.